The Role and Mechanism of Cinnamon for Athlete Metabolism and Recovery Process: A Systematic Literature Review - Muhamad Fahmi Hasan; I Ketut Adnyana; Samsul Bahri; Hamidie Ronald Daniel Ray (Universitas Pendidikan Indonesia, 2022)
Athletes have a high need to maintain their performance to stay fit while performing a high training intensity and frequent exercise. It makes athletes have a high need for supplements. However, athletes are prohibited from taking supplements included in the doping category. The lowest risk of doping is herbal-based supplements. This study used a systematic review method. The screening employed the PRISMA method as the preferred reporting item for systematic review and meta-analyses. The articles were obtained from Scopus and Dimensions databases using “cinnamon” as the keyword. Furthermore, the words